Dual mode (upconversion and downshifting) behavior of Ho3+/Yb3+/Bi3+ co-doped YTaO4 phosphor and its application as a security ink - Roy A.; Dwivedi A.; Mishra H.; Kumar D.; Rai S.B. (My University, 2025)
The Ho3+/Yb3+ co-doped YTaO4 phosphor has been synthesized in absence and presence of Bi3+ ion using high temperature solid state reaction method. X-ray diffraction (XRD) patterns confirm the pure phase formation of the synthesized materials. The vibrational behavior of the samples is studied by Fourier Transform Infrared (FTIR) spectroscopy, which suggests the phonon frequency of the material about 625 cm−1. The direct optical band gap of the synthesized phosphor has been calculated using UV–Vis absorption spectrum and the value is found to be 4.80 eV. However, the value of band gap is reduced in presence of Bi3+ ions (4.26 eV). Ho3+/Yb3+ co-doped YTaO4 phosphor shows intense green and weak red upconversion emissions on 980 nm excitation. Ho3+/Yb3+ co-doped YTaO4 phosphor sample also shows intense green and weak red emissions on 450 nm excitation. The downshifting emission is enhanced two to three times in presence of Bi3+ due to metal to metal charge transfer self activation of the host. However, the UC emission intensity almost remains unchanged even in presence of Bi3+. Bi3+ ion also shows an intense broad blue emission on UV excitation. The Ho3+/Yb3+ co-doped YTaO4 phosphor sample has been used for security ink applications in green region via 980 nm excitations and in blue region in presence of Bi3+ via UV (365 nm) excitation. Thus, the dual mode emission of this phosphor is applicable for security ink applications in two different regions. This material also permits one to get an intense tunable radiation from 350 to 650 nm on excitation with 342 nm. There are very few dye lasers, which emit intense tunable radiation in this wavelength region in such a wide wavelength range. © 2019 Elsevier B.V.